2020
DOI: 10.1101/2020.07.10.193003
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selective cross-linking of coinciding protein assemblies by in-gel cross-linking mass-spectrometry

Abstract: Cross-linking mass spectrometry has developed into an important method to study protein structures and interactions. The in-solution cross-linking workflows involve time and sample consuming steps and do not provide sensible solutions for differentiating cross-links obtained from co-occurring protein oligomers, complexes, or conformers. Here we developed a cross-linking workflow combining blue native PAGE with in-gel cross-linking mass spectrometry (IGX-MS). This workflow circumvents steps, such as buf… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 79 publications
2
11
0
Order By: Relevance
“…We analyzed the organization and interaction landscape of protein complexes in bovine heart mitochondria by combining cross-linking mass spectrometry XL-MS and complexome profiling (Heide et al, 2012;Hevler et al, 2021) thereby adding new information on native state multiprotein complexes of interest, building upon previous work exploring the interactome of mitochondria from different organisms, tissues and cells by XL-MS (Chavez et al, 2020;Linden et al, 2020;Liu et al, 2018;Ryl et al, 2020;Schweppe et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We analyzed the organization and interaction landscape of protein complexes in bovine heart mitochondria by combining cross-linking mass spectrometry XL-MS and complexome profiling (Heide et al, 2012;Hevler et al, 2021) thereby adding new information on native state multiprotein complexes of interest, building upon previous work exploring the interactome of mitochondria from different organisms, tissues and cells by XL-MS (Chavez et al, 2020;Linden et al, 2020;Liu et al, 2018;Ryl et al, 2020;Schweppe et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial membranes from bovine heart were isolated and preserved as described in (Hevler et al, 2021). In order to increase the purity of the preparation and for Tris-buffer removal, frozen crude mitochondria (4 x 15 ml aliquots; 60 mg protein/ml) were thawed on ice, diluted (1:4) with ice-cold SEH buffer (250 mM sucrose, 1 mM EDTA, 20 mM HEPES, pH 7.4 adjusted with NaOH) and centrifuged at 1,000 x g (10 min; 4°C).…”
Section: Isolation and Purification Of Bovine Heart Mitochondria (Bhm)mentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the other MAC components, the only known high-resolution structure of C7 is from the fully assembled MAC [9]. The much bettercharacterized C6, the closest homolog of C7, can adopt various conformations in its soluble state [5,7,9,13]. Based on the sequence and domain similarities between C6 and C7, it is tempting to speculate that the soluble C7 could also possess this conformational flexibility.…”
mentioning
confidence: 99%
“…This study examines the structure and proteoform profile of C7 by an integrative structural MS-based approach combining native MS, glycopeptide-centric MS, in-gel cross-linking MS (IGX-MS) [13], and structural modelling. Furthermore, we present the proteome profile of C6 and extend on our earlier work, where we showed that C6 adapts a compact conformation in solution [13]. Comparisons to the C6 structure reveals, as expected, an overall high similarity in structure and domain organization.…”
mentioning
confidence: 99%